Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.5194/bg-2-141-2005
|View full text |Cite
|
Sign up to set email alerts
|

Submarine groundwater discharge to a small estuary estimated from radon and salinity measurements and a box model

Abstract: Abstract. Submarine groundwater discharge was quantified by a variety of methods for a 4-day period during the early summer of 2004, in Salt Pond, adjacent to Nauset Marsh, on Cape Cod, USA. Discharge estimates based on radon and salinity took advantage of the presence of the narrow channel connecting Salt Pond to Nauset Marsh, which allowed constructing whole-pond mass balances as water flowed in and out due to tidal fluctuations. The data suggest that less than one quarter of the discharge in the vicinity of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Crusius et al, 2005;Santos et al, 2009;Taniguchi, 2002). Similarly, rapid variations in groundwater fluxes have been observed in lakes in response to factors such as seiching and precipitation (Rosenberry et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Crusius et al, 2005;Santos et al, 2009;Taniguchi, 2002). Similarly, rapid variations in groundwater fluxes have been observed in lakes in response to factors such as seiching and precipitation (Rosenberry et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…A preliminary study in the Great Barrier Reef indicated that continuously measured radon along a coastline can be used as an indicator for the presence of SGD (Stieglitz, 2005). Burnett et al (2008) mapped radon in a coastal embayment along the Ubatuba coastline in Brazil, and Crusius et al (2005) estimated SGD discharge rates based on concurrently measured radon and salinity. Here a multi-detector field setup is evaluated for the spatial mapping of radon on a still larger spatial scale, and it is discussed how continuous mapping of this tracer, in combination with ocean water salinity, can be used to efficiently infer and interpret locations of radon input to the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…These include integrated marine seismic and marine electrical resistivity surveys to establish submarine groundwater salinity distribution in a hydrogeologic framework Manheim et al 2004); coring and sampling in offshore wells to analyze nutrients, stable isotopes, and groundwater age tracers, including tritium, tritium/helium, sulfur hexafluoride, and chlorofluorocarbons ); and natural groundwater tracer studies using radon gas emanation to evaluate groundwater discharge locations, rates of discharge, and time variability over tidal cycles (Crusius et al 2005). These and many other useful techniques for measuring and understanding groundwater in coastal regions, some of which were incorporated in our study of the NRE, are presented in Burnett et al (2006).…”
Section: Site Description and Backgroundmentioning
confidence: 99%